2007
DOI: 10.1111/j.1365-2672.2007.03461.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and functional analysis of a novel gene cluster involved in biphenyl degradation in Rhodococcus sp. strain R04

Abstract: Aims:  Isolation of the genes relative to PCB biodegradation and identification of the bph gene function in Rhodococcus sp. R04. Methods and Results:  A 8·7‐kb fragment carrying the biphenyl catabolic genes bphABCD was isolated from the gene library in Rhodococcus sp. R04. Based on the deduced amino acid sequence homology, seven bph genes, bphA1A2A3A4, bphB, bphC and bphD, were thought to be responsible for the initial four steps of biphenyl degradation. In Escherichia coli, BphA exhibited poor activity for bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 50 publications
0
11
0
1
Order By: Relevance
“…However, strain of R. jostii have multiple pathways like bph and etb gene cluster [36]. Presence of bph, etb and nar gene cluster in CETP metagenome dataset and also identify the bacterial strain according to previous report suggested that the e uent contain chlorinated compounds [36] [37].…”
Section: Discussionmentioning
confidence: 90%
“…However, strain of R. jostii have multiple pathways like bph and etb gene cluster [36]. Presence of bph, etb and nar gene cluster in CETP metagenome dataset and also identify the bacterial strain according to previous report suggested that the e uent contain chlorinated compounds [36] [37].…”
Section: Discussionmentioning
confidence: 90%
“…R04 during degradation of diverse chlorobiphenyls (Yang et al 2004(Yang et al , 2007. 3-CBA and 4-CBA were, respectively monitored by GC-MS in cultures from strain R04 grown on 3-chlorobiphenyl and 4-chlorobiphenyl (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…strain R04 and Rhodococcus sp. strain K37 [10,12]. Among these gene clusters, the bphC gene encoding 2,3-dihydroxybiphenyl-1,2-dioxygenase is responsible for the ring cleavage of 2,3-dihydroxybiphenyl, which is a critical step in the aerobic degradation of biphenyl by bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that more than 1.5 million tons of PCBs have been manufactured worldwide [1,2]. PCBs have potential health risks for living organisms due to resulted benzoate and 2-hydroxy-penta-2,4-dienoate are subjected to the downstream pathway and the further metabolism of tricarboxylic acid cycle [8][9][10][11][12]. The genes encoding the enzymes for biphenyl degradation are clustered and termed as bph gene cluster, which could be divided into four types based on its genetic organization.…”
Section: Introductionmentioning
confidence: 99%